A three-level graph-based model for the management of hospital information systems - Winter, Alfred; Haux, Reinhold (Methods of information in medicine, 1995)
Information processing in hospitals, especially in university hospitals, is currently faced with two major issues: low-cost hardware and progress in networking technology leads to a further decentralization of computing capacity, due to the increasing need for information processing in hospitals and due to economic restrictions, it is necessary to use, commercial software products. This leads to heterogeneous hospital information systems using a variety of software and hardware products, and to a stronger demand for integrating these products and, in general, for a dedicated methodology for the management of hospital information systems to support patient care and medical research. We present a three-level graph-based model (3LGM) to support the systematic management of hospital information systems. 3LGM can serve as a basis for assessing the quality of information processing in hospitals. 3LGM distinguishes between a procedural level for describing the information procedures (and their information interchange) of a hospital information system and thus its functionality, a logical tool level, focusing on application systems and communication links, and a physical tool level with physical subsystems (e.g., computer systems) and data transmission. The examples that are presented have been taken from the Heidelberg University Hospital Information System.